2021
DOI: 10.1007/s13238-021-00825-y
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation-based sperm clusters mediate sperm oviduct entry and fertilization

Abstract: contains supplementary material, which is available to authorized users.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…The authors in [19] found evidence that clustering of sperm is functionally important for fertilization potential and our model demonstrates that there is certainly an advantage to clustering or swimming together in terms of velocity and efficiency. With respect to sperm trains specifically, when we time-average over entire simulations, we observe substantial increases in velocities for sperm trains when compared to individuals.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…The authors in [19] found evidence that clustering of sperm is functionally important for fertilization potential and our model demonstrates that there is certainly an advantage to clustering or swimming together in terms of velocity and efficiency. With respect to sperm trains specifically, when we time-average over entire simulations, we observe substantial increases in velocities for sperm trains when compared to individuals.…”
mentioning
confidence: 50%
“…Figure 1a shows one example of a chiral ribbon trajectory observed in human sperm. Species as diverse as deer mouse, cattle, fly, echidna and opossum have sperm that can collectively swim together [12][13][14][15][16][17][18][19]. Figure 1b shows an example of such behavior in the deer mouse, where apical hooks on sperm heads enable sperm to attach to a neighbor's flagellum.…”
Section: Introductionmentioning
confidence: 99%
“…How such a slow flagellar beat is able to propel spermatozoa forward is another mystery. Qu et al [ 17 ] saw numerous mouse spermatozoa with their heads abutted against the epithelium of the UTJ. They speculated that spermatozoa clustering together in such an orientation and beating their tails synchronously enable the spermatozoa to move into the UTJ.…”
Section: Transport Of Rodent Spermatozoa Through the Vagina Uterus An...mentioning
confidence: 99%
“…Surprisingly, while investigating the functions of spermspecific proteins in gene knockout (KO) mouse strains, it was found that a certain strain of KO sperm with normal morphology and motility were unable to pass through the UTJ [117]. Subsequently, the deletion of genes for a number of sperm-specific proteins resulted in the same infertile male phenotype [118]. The proteins produced by these genes were either plasma membrane proteins or were involved in bringing proteins to the plasma membrane.…”
Section: Apparent Co-evolution Of Sperm and Female Reproductive Tract Physical Traitsmentioning
confidence: 99%
“…This seemed to indicate that sperm passage through the UTJ might involve some sort of molecular interaction between one or more sperm proteins and receptors lining the oviduct. However, recently, evidence has arisen to indicate that the proteins play a role in aggregating sperm in the uterus, and it has been proposed that the aggregated sperm, which are aligned in the same direction, are able to push their way into the UTJ, or push open the UTJ, which is something that single sperm seem unable to do [118]. This interesting discovery requires further investigation as a previously unknown function of sperm aggregation.…”
Section: Apparent Co-evolution Of Sperm and Female Reproductive Tract Physical Traitsmentioning
confidence: 99%